Nutritional needs, resources, and barriers among unhoused adults cared for by a street medicine organization in Chicago, Illinois: a cross-sectional study - Elizabeth J. Adams; Michelle Lu; Richard Duan; Alyssa K. Chao; Helen C. Kessler; Charles D. Miller; Adam G. Richter; Daniel G. Latyshev; Jehannaz D. Dastoor; Adam J. Eckburg; Namrata S. Kadambi; Nila R. Suresh; et al. (BMC, 2023)
Abstract Background Those experiencing houselessness rely on obtaining food from community organizers and donations. Simultaneously, the houseless face disproportionally high rates of medical conditions that may be affected by diet including diabetes, hypertension, and hyperlipidemia. There is limited literature on the resources and barriers of the houseless community regarding optimal nutrition from an actionable perspective. Further, less data is available on how street medicine organizations may best impact the nutrition of the unhoused they serve. Elucidating this information will inform how organizational efforts may best support the nutrition of the houseless community. Methods In partnership with the medical student-run organization, Chicago Street Medicine, at Northwestern University Feinberg School of Medicine, twenty adults experiencing houselessness in Chicago, Illinois participated in the cross-sectional study. A 10-item survey was verbally administered to characterize the participants' daily food intake, food sources, barriers, resources, and nutritional preferences and needs. All data was directly transcribed into REDCap. Descriptive statistics were generated. Results Individuals consumed a median of 2 snacks and meals per day (IQR: 1-3). No participant consumed adequate servings of every food group, with only one participant meeting the dietary intake requirements for one food group. Participants most often received their food from donations (n = 15), purchasing themselves (n = 11), food pantries (n = 4), and shelters (n = 3). Eleven of nineteen participants endorsed dental concerns as a major barrier to consuming certain foods. Twelve participants had access to a can opener and twelve could heat their meals on a stove or microwave. Seven had access to kitchen facilities where they may prepare a meal. Approximately half of participants had been counseled by a physician to maintain a particular diet, with most related to reducing sugar intake. Conclusion Most houseless participants were unable to acquire a balanced diet and often relied on organizational efforts to eat. Organizations should consider the chronic health conditions, dentition needs, and physical resources and barriers to optimal nutrition when obtaining food to distribute to the unhoused.